Объяснение:
а) (*- 2b) ^2= 100 – 40b + 4b^2
(10 - 2b)^2 = 100 – 40b + 4b^2
6) (9x - *)^2 = 81х -108xy + 36у^2
(9x - 6y) = 81х^2 -108xy + 36у^2
в) (15х + *) = 225х + 12xy +0,16y:
(15х + 0,4 y) ^2= 225х^2 + 12xy +0,16y^2
г) (2,5а +3 b)^2 = 6,25a^2 + * + 9b^2.
(2,5а +3 b)^2 = 6,25a^2 + 15 ab+ 9b^2.
Объяснение:
а) (*- 2b) ^2= 100 – 40b + 4b^2
(10 - 2b)^2 = 100 – 40b + 4b^2
6) (9x - *)^2 = 81х -108xy + 36у^2
(9x - 6y) = 81х^2 -108xy + 36у^2
в) (15х + *) = 225х + 12xy +0,16y:
(15х + 0,4 y) ^2= 225х^2 + 12xy +0,16y^2
г) (2,5а +3 b)^2 = 6,25a^2 + * + 9b^2.
(2,5а +3 b)^2 = 6,25a^2 + 15 ab+ 9b^2.